(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This paper articulates body dramaturgy and mechanisms that develop the creative autonomy of the performer, valuing the somatic and affective content of the actor/dancer’s corporeality as an embodied scenic thinking. Through dance dramaturgy discourse of different authors, it is supported that the scenic thinking of the interpreter-creator can be seen as dramaturgical attitude in the artistic making. Coming from an empirical research about performer training, the dramaturgy of the performer is exemplified through laboratory practices supported by Preston-Dunlop and Sanchez-Colberg’s (2010) Choreological Studies, and a creative process that resulted in a dance theatre performance.